Serum Transferrin Receptor and Transferrin Receptor-Ferritin Index Identify Healthy Subjects With Subclinical Iron Deficits - Suominen, Pauli; Punnonen, Kari; Rajamäki, Allan; Irjala, Kerttu (Blood, 1998)
Despite the established utility of serum transferrin receptor (sTfR), serum ferritin, and the sTfR/log ferritin ratio (TfR-F Index) in the diagnosis of iron deficiency (ID) anemia, the numeric values of these parameters, which are indicative of subclinical ID, remain to be clearly defined. In this study, 65 apparently healthy nonanemic adults (22 men and 43 women) were treated with 3 months of oral iron supplementation to evaluate its effect on parameters reflecting iron status and to determine the prevalence of subclinical iron deficiency in apparently healthy adults. Significant supplementation-induced changes were observed in sTfR, ferritin, and TfR-F Index values in women, whereas in men, none of the studied parameters showed any significant change. Iron-deficient erythropoiesis (IDE) was not observed in men, but was found in 17 women (40%). Although individuals with a compromised iron status may be represented in substantial numbers in conventional reference populations, they can be readily identified using sTfR, ferritin, and TfR-F Index determinations. © 1998 by The American Society of Hematology.